Conflict Mobilization in Social Networks Communities as an Actual Practice of Protest Communication: Collective-Personal Dimension - L. N. Rebrina (Научный диалог, 2021)
The results of the analysis of the collectivepersonal dimension ofthe conflict mobilization realized in the communities of social networks as an actual practice of protest communication are presented. The interactive tools of communities of conflict mobilization as actors of protest communication; correlations between various statistical parameters of communities are characterized. The types of publications that form the content of communities have been determined. The main tools for the formation of Internet solidarity, the patterns of virtual interaction regulated by the “we-they” model are presented. Methods and means of explication ofthe addresser and addressee in different types of publications are described. The conclusion is made about the prevalence of ascertaining and regulated communicative actions in the communicative behavior of the addresser; dominance of psychological argumentation; frequent implementation of a phatic strategy through consolidating calls to community members; about the least representation of the strategy of self-presentation, actualized mainly through its identification with a mass addressee and presentation of the group’s collective position. It is shown that the addressee most often performs dramatic and regulated communicative actions; characterized by active self-presentation through the presentation of a subjective position, solidarizing identification and opposition to a common opponent; preference for ethical and emotional arguments; various phatic tactics.